ANALISIS POLA KALIMAT PADA DONGENG MUNI PENIUP TEROMPET KARYA ENDANG FIRDAUS - Ida Basaria; Emia Annisa Br Ginting; Firda Elisa; Uswatun Hasanah Subekhi (Yayasan Nuraini Ibrahim Mandiri, 2024)
A sentence is the smallest unit of language, in oral or written form, and capable of expressing a complete thought. Fairy tales are fictional stories that not only contain moral values, but are also made to entertain. This research was conducted with the aim of analyzing the sentence patterns in the fairy tale “Muni Peniup Terompet” by Endang Firdaus using descriptive qualitative research methods. In this research, secondary data was used and data collection was carried out using observation and analysis methods, then carrying out reading and note-taking techniques. The results of this research contain sentence patterns in the fairy tale texts being analyzed. The sentence patterns found are: 1) S and P; 2) S-P and O; 3) S-P-O and K; 4) K-S-P and O; and 5) K-S-P and K. Keywords: Sentence, Sentence Patterns, Fairy Tale